LncRNA-MALAT 1 regulates cardiomyocyte scorching in diabetic cardiomyopathy by targeting NLRP3 - Shi, Chang; Wu, Lifang; Li, Ling (Cellular and Molecular Biology, 2022)
Diabetic cardiomyopathy (DCM) is a common complication of diabetes mellitus, often leading to heart failure, arrhythmias and sudden death. Long-stranded non-coding RNA (LncRNA), an endogenous non-coding long-stranded RNA, is associated with diabetic cardiomyopathy. However, the mechanism of LncRNA regulation of cellular scorching in diabetic cardiomyopathy remains unclear. This study aimed to elucidate whether MALAT 1 affects cardiomyocyte scorching in DCM patients. Methods: Streptozotocin (STZ) at 35 mg/Kg was used to induce diabetes in rats. H9C2 cardiomyocytes and primary cardiomyocytes (PCM) were cultured at 5.5 and 50 mmol/L glucose, respectively. The expression levels of MALAT 1 and scorch death-related genes were detected by RT-PCR using plasmids to suppress or overexpress the related genes, respectively. Immunofluorescence, RT-PCR and Western blot were used to detect the extent of cell scorch death. RESULTS: MALAT 1 expression was elevated in diabetic and high glucose-induced cardiomyocytes and myocardial tissue from diabetic mice (p<0.001). Silencing of MALAT 1 alleviated cardiomyocyte scorch death by targeting NLRP3. Furthermore, silencing MALAT 1 reduced cell death and improved cardiac function and morphology. CONCLUSIONS: MALAT 1 is overexpressed in DCM and silencing MALAT 1 inhibits cell scorch death by affecting NLRP3 expression. We clarify for the first time that MALAT 1 may be a new therapeutic target for DCM.